2019
DOI: 10.1155/2019/7891359
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Beta Cell Function in Adults of Black African Ethnicity

Abstract: Background Understanding ethnic differences in beta cell function has important implications for preventative and therapeutic strategies in populations at high risk of type 2 diabetes (T2D). The existing literature, largely drawn from work in children and adolescents, suggests that beta cell function in black African (BA) populations is upregulated when compared to white Europeans (WE). Methods A systematic literature search was undertaken in June 2018 to identify comparative studies of beta cell function betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 91 publications
(203 reference statements)
0
27
1
Order By: Relevance
“…An earlier study showed that insulin and C-peptide levels were increased in obese individuals compared to lean controls and suggested obese subjects have an impaired glucose homeostasis and exhibit prediabetic factors, including hyperinsulinemia, and insulin resistance (26)(27)(28)(29). Glucagon levels were elevated in obese individuals (26).…”
Section: Discussionmentioning
confidence: 98%
“…An earlier study showed that insulin and C-peptide levels were increased in obese individuals compared to lean controls and suggested obese subjects have an impaired glucose homeostasis and exhibit prediabetic factors, including hyperinsulinemia, and insulin resistance (26)(27)(28)(29). Glucagon levels were elevated in obese individuals (26).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth considering that the paucity of male participants in this area of the literature may have led to an overestimation of ethnic differences in insulin secretory response. 48 We found that the peripheral hyperinsulinaemia of our BA population was attributable to the ethnic difference in insulin clearance; furthermore, this difference persisted after adjustment for insulin sensitivity, hepatic fat content and insulin secretion rate. While insulin clearance was associated with IHL and whole-body and hepatic insulin sensitivity in WE men, these associations were absent in BA men.…”
Section: Discussionmentioning
confidence: 60%
“…Two other adult non‐diabetic all‐male studies have examined ethnic differences in insulin responses 46,47 ; neither found increased insulin secretion in subjects of African ancestry compared with white subjects, consistent with our findings. It is worth considering that the paucity of male participants in this area of the literature may have led to an overestimation of ethnic differences in insulin secretory response 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aradillas-García et al found, however, that during childhood and adolescence, insulin concentrations and HOMA-IR exhibited a gradual increase with age [86]. This discrepancy in results may be due to multiple factors, including ethnicity [87] [88] [89] and confounding factors associated with aging such as obesity, decreased physical activity, medications and co-morbidities. World Journal of Cardiovascular Diseases…”
Section: Fernström Et Al Found An Inverse Association Between Homairmentioning
confidence: 99%